The significance of the geological strata on desert runoff agriculture: Indications for stable desert environment over the last 1600 years in southern Israel. (December 2016) - Wieler, Nimrod; Avni, Yoav; Rosensaft, Marcelo
Abstract: Large distribution of historical agricultural installations in the desert zone of the southern Levant, mainly from the Byzantine - Early Muslim periods (1600–1000 y BP) indicates that the region was highly productive in the past. That could have been achieved either because of a more humid climate, or by sophisticated runoff harvesting techniques utilized by the ancient farmers under a desert climate. Among all, the most important factor enabling the existence of the desert agriculture was runoff harvesting. Our study assess a multi-disciplinary approach testing the relationship between diverse geological strata, their ability to cause runoff and the possible preferences made by the ancient farmers to utilize these rock properties. Utilizing GIS methods we generated high-resolution maps, highlighting the present runoff potential both on a single lithology slope level and on the drainage basin scale. By applying this methodology we show that high correlation (80%) exists when testing the spatial emplacement of runoff-farming installations constructed during the Byzantine - Early Muslim periods on the present best runoff yielding drainage basins under the present climatic conditions. This hints at the long stability of the environmental and probably climatic conditions in the southern Levant regions during the late Holocene. Highlights: Multi-disciplinary approach enabled testing the relationship between geological strata, runoff yield and ancient agriculture farms. Utilizing GIS methods we generated high-resolution runoff maps for both single lithology slope level and drainage basin scale. Geological strata plays a key role effecting the locations of ancient agriculture installations located in arid regions. Our findings hints on long-term stable climate environment prevailing in the southern Levant regions during the late Holocene.